Konteks dan Corak Mistisisme Islam dalam Tradisi Keagamaan Masyarakat Gorontalo - Mashadi Mashadi (Ulumuna, 2013)
Many studies on religion generally focus on two important points. The first is the discussion about God and His Attributes, such as invisible, sacred and absolute. The second point relates to social dimensions of religion which are profane, empirical and relative. These are two points that this paper attempts to reveal when elucidating mysticism in the context of Muslim local tradition in Gorontalo. This study shows that Muslim ritual traditions of Gorontalo are deeply influenced by Sufi order’s mysticisms and practices. These traditions are expressed in various local rituals and cultures. This integration of religion and culture affirms the pattern of religious expression which is unique and localized. The appreciation of the existence of God in this locale is realized through the chanting and supplication to the souls of forebears and through the event of public gratitude when the people are blessed with abundant bounties.